2022
DOI: 10.1021/acs.energyfuels.2c01230
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Combustion Study of Ethanol Over Manganese Oxides with Different Morphologies

Abstract: Ethanol is extensively used in the transport field as a clean additive and alternative for gasoline in internal combustion engines, although its incomplete combustion inevitably releases harmful species to humans and the environment. Mn-based oxides, one of the most promising materials for catalytic combustion, have attracted considerable interest due to their excellent catalytic performance and low cost. In this work, hydrothermal methods were used to synthesize the different manganese oxides with distinct mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 72 publications
(105 reference statements)
0
5
0
Order By: Relevance
“…AMO-250 presents three reduction peaks located at 232, 301, and 424 °C. The peak centered at 232 and 301 °C is associated with the reduction of Mn 4+ to Mn 3+ , and the peak at 424 °C is attributed to the reduction of Mn 3+ to Mn 2+ . , The spectrum of AMO-400 shows a similar phenomenon, and the peaks shift to a higher reduction temperature. Three reduction peaks are detected over AMO-500 and AMO-700 at higher temperatures due to the enhancement of the Mn–O bond by high-temperature activation.…”
Section: Resultsmentioning
confidence: 85%
“…AMO-250 presents three reduction peaks located at 232, 301, and 424 °C. The peak centered at 232 and 301 °C is associated with the reduction of Mn 4+ to Mn 3+ , and the peak at 424 °C is attributed to the reduction of Mn 3+ to Mn 2+ . , The spectrum of AMO-400 shows a similar phenomenon, and the peaks shift to a higher reduction temperature. Three reduction peaks are detected over AMO-500 and AMO-700 at higher temperatures due to the enhancement of the Mn–O bond by high-temperature activation.…”
Section: Resultsmentioning
confidence: 85%
“…Which might be due the catalysts has been deactivated due to with the reaction with toluene for long periods 18 . As depicted in Figure 6, 19,20 performance of the catalyst decreases as the reaction proceeds at the same temperature. This is because when the concentration of toluene was high, oxygen consumption increased.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, Peng et al reported that MnO 2 /NCNT composites demonstrated exceptional catalytic activity for the oxidative decomposition of 100 ppm of HCHO at elevated temperatures, which directly deposited MnO 2 on the surface of NCNT using an in situ oxidation method . Numerous studies have been conducted to fabricate composites, control surface morphology, and regulate the type of defects and microstructure of Mn-based catalysts to improve their catalytic efficiency. , The development of high-performance catalysts that can fully oxidize HCHO at ambient temperatures is crucial for their commercial implementation. Previous achievements have shown that the construction of surface V O can improve the formation of activated oxygen species and accelerate pollutant decomposition. , According to previous works, the adsorption strategy, using zeolite and activated carbon, has been regarded as an economic strategy for HCHO removal, but the single adsorption effect is only useful for a short time.…”
Section: Introductionmentioning
confidence: 99%
“…13 Numerous studies have been conducted to fabricate composites, control surface morphology, and regulate the type of defects and microstructure of Mn-based catalysts to improve their catalytic efficiency. 9,14 The development of high-performance catalysts that can fully oxidize HCHO at ambient temperatures is crucial for their commercial implementation. Previous achievements have shown that the construction of surface V O can improve the formation of activated oxygen species and accelerate pollutant decomposition.…”
Section: Introductionmentioning
confidence: 99%